2005
DOI: 10.1038/sj.bjc.6602834
|View full text |Cite
|
Sign up to set email alerts
|

Microarray comparative genomic hybridisation analysis of intraocular uveal melanomas identifies distinctive imbalances associated with loss of chromosome 3

Abstract: Defining regions of genomic imbalance can identify genes involved in tumour development. Conventional cytogenetics has identified several nonrandom copy number alterations (CNA) in uveal melanomas (UVM), which include monosomy 3, chromosome 6 abnormalities and gain of 8q. To gain further insight into the CNAs and define the regions involved more precisely we analysed 18 primary UVMs using 1 Mb BAC microarray comparative genomic hybridisation (CGH). Our analysis showed that the most common genomic imbalances we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…This analysis confirmed that 3-and 6p+ represent almost mutually exclusive alterations and thereby provided further support to the idea that 3-and 6p+ signify alternative pathogenetic sequences, as previously suggested (22,25,26). In addition, we identified a third subgroup, representing f18% of all tumors, which were normal for chromosomes 3 and 6p.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This analysis confirmed that 3-and 6p+ represent almost mutually exclusive alterations and thereby provided further support to the idea that 3-and 6p+ signify alternative pathogenetic sequences, as previously suggested (22,25,26). In addition, we identified a third subgroup, representing f18% of all tumors, which were normal for chromosomes 3 and 6p.…”
Section: Discussionsupporting
confidence: 71%
“…Although other studies have identified discrete patterns of chromosomal alterations in UM (4,12,14,20,22), this study used statistical ''pattern recognition'' techniques to organize chromosomal alterations into significant groupings. This analysis confirmed that 3-and 6p+ represent almost mutually exclusive alterations and thereby provided further support to the idea that 3-and 6p+ signify alternative pathogenetic sequences, as previously suggested (22,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Of various cytogenetic abnormalities observed, monosomy 3 is the strongest predictor of metastatic risk. [5][6][7][8][9][10][11][12][13][14] Several techniques are currently being used to detect monosomy 3 and other chromosomal changes associated with the development of metastatic disease. Gene-expression profiling is also being used in prognostication.…”
Section: Results Monosomy 3 Was Detected By Fish-cep3 In 27 Tumorsmentioning
confidence: 99%
“…For primary glioblastoma-specific MCRs, there are 23 gains/amplifications with a median size of 0.87 Mb and median number of 13 genes. Of these 23 loci, 6 represent loci that have been significantly narrowed and 11 loci have not been described in glioblastoma, yet their cancer relevance is reinforced by validated connections to other cancer types such 2p25 in ganglioneuroblastoma (29), 6p25 in uveal melanoma (30), and 17q21 in medulloblastoma (ref. 31; Table 2).…”
Section: Comparison Of Primary and Secondary Glioblastoma Genomic Promentioning
confidence: 99%